Control of anxiety in the pre and post operative of bariatric surgery (Research, Society and Development, 2022)
Anxiety may be associated with an increased risk of developing obesity, as it can cause changes in cortisol production in stressful situations. Objective: to identify sociodemographic and clinical aspects, BMI, and the association with the presence of comorbidity in patients with anxiety who underwent bariatric surgery. Method: cross-sectional study, survey type. We used an online questionnaire through the Google Forms platform assessing before and after surgery. Results: sample composed of 5,160 participants, divided into four groups: group A, 1,796 individuals who had no anxiety and did not develop anxiety after surgery; group B, 410 individuals who had anxiety and remained; group C, 1,391 who had anxiety and improved and group D with 1563 participants who had no anxiety and developed after surgery.  The mean age was 37.25 years, female prevalence, married, from the southeastern region. In all groups there was a significant reduction in smoking, alcohol consumption and greater adherence to physical activity after surgery. The gastric bypass technique was the most prevalent. It was observed that group D developed anxiety after surgery and improvement in preexisting comorbidities. Dumping syndrome was more prevalent in groups B and D. Conclusion Bariatric surgery favors improvement in anxiety levels and preexisting comorbidities, however, it is possible that it is a risk factor for the emergence of anxiety in those who did not present it before the intervention.